Mediated Bordering : Eurosur, the Refugee Boat, and the Construction of an External EU Border - Ellebrecht, Sabrina (2020)
The external border of the EU remains under permanent construction. Sabrina Ellebrecht engages with two of its primary building sites - the European Border Surveillance System (Eurosur) and the Refugee Boat. She analyzes how the function and quality of the EU's current political border is crafted, shaped, produced and eventually stabilized through these two mediators. Eurosur and the Refugee Boat mediate a level of Europeanization which has hitherto - and would otherwise have - been impossible. While Eurosur mobilizes the limits of border policing in various ways, the Refugee Boat functions as the vacillating European Other to legitimize both control and humanitarian interventions. The study shows the specific, if not constitutive, ambivalences of EU border policies, and explores the emergence of viapolitics.